Evaluation of Quality of Life among the Geriatric Population in Rural Regions Following the COVID-19 Pandemic - Gaikwad, Rajesh Anandrao; Durgawale, Prakash M. (Journal of Neonatal Surgery, 2025)
Background: Aging is a natural and inevitable biological process characterized by a steady decline in physical and mental functions. The World Health Organization (WHO) defines aging as a series of progressive changes that lead to diminished physical and cognitive capabilities, increased susceptibility to illnesses, and ultimately, mortality. With advancements in healthcare and declining birth rates worldwide, there is a notable rise in the global elderly population. Objectives To estimate the proportion of elderly individuals residing in rural areas. To examine the morbidity patterns among the elderly and explore their relationship with socio-demographic variables. To evaluate the quality of life (QoL) of the elderly during the defined study period. To recommend strategies for enhancing health and well-being among the rural elderly population. Methodology: This research was carried out as a community-based, cross-sectional study using a multistage sampling method. The target population consisted of individuals aged 60 and above, comprising 5% of the rural population (estimated at 550). To ensure adequate representation, the study aimed to include at least 90% of the elderly population, accounting for a potential 10% non-response rate. The study was conducted in selected rural areas of Satara District, Maharashtra, India. Ethical consent was obtained from all participants. Data collection was carried out using standardized tools, and both descriptive and inferential statistical methods were employed for analysis. Results: Among the 550 elderly participants, the majority fell within the 60–69 age group, with no significant differences observed between rural and urban distributions (p = 0.803), suggesting a uniform aging pattern. Gender distribution in rural areas was also balanced, with males accounting for 71.7% of participants, showing no significant variation across locations. Conclusion: The findings revealed that elderly individuals in rural areas generally experienced a higher quality of life than their urban peers, particularly in terms of psychological well-being, social engagement, and overall life satisfaction. Key demographic variables such as age, gender, and body mass index (BMI) did not significantly influence QoL. However, socioeconomic conditions and family support systems played a more impactful role. Addictive behaviors and co-existing illnesses were more detrimental in urban areas, although the general quality of life across different groups remained relatively stable.